Skrining Aktivitas Antibakteri dan Identifikasi Molekuler Berdasarkan Gen 16S rRNA Isolat Aktinomiset Asal Pulau Enggano dan Bali - Nadina, Rahmah Qisti; Pujiyanto, Sri; Wijanarka, W; Fahrurrozi, Fahrurrozi (Berkala Bioteknologi, 2019)
Actinomycetes are a Gram positive bacteria who plays an important role in pharmaceutical industry because of its ability to produce an antibacterial compound. This study aims to select actynomycetes isolates that has antibacterial activity and to identify the isolates based on 16S rRNA gene squence. The actinomycetes isolates were inoculated using ISP-2 medium and cultured in SYP (starch, yeast, peptone) media for 13 days. The cultures were extracted using etyl acetate solvent and antibacterial activity was tested against Bacillus subtilis and Escherichia coliusing agar diffusion method.Positive isolates were identified based on 16S rRNA gene sequence. The 16S rRNA gene from positive isolates was sequenced and analyzed with computerized help and was deposited at NCBI. The antibacterial activity test revealed 5 from 22 isolates had an antebacterial activity shown by the clear zone around the whatman filter paper on both tested bacteria. The identification revealed these five isolates were identified asStreptomyces mutabilis, Streptomyces sp, and Streptomyces griseorubens. This study shows these isolates from Enggano and Bali Island are potential as antibacteri producer. Keywords : actynomycetes, antibacterial activity, 16S rRNA